Microspheres for drug-delivery to the colon - Watts, Peter James (1992)
The work described in this thesis is concerned with the design and evaluation of microsphere-based systems for drug delivery into the colon. In initial experiments, techniques were devised for the preparation of microspheres from two sustained-release acrylic polymers, Eudragits RL and RS, using emulsification-solvent evaporation techniques. For Eudragit RS microspheres containing the drug 5-aminosalicylic acid, the rate of drug release could be controlled by the type and concentration of surfactant used for preparation. Consequently, formulations could be produced which released encapsulated drug instantaneously or over many hours. The surfactants may have been altering the structure of the microsphere drug-polymer matrix. Two novel analytical techniques were employed to characterise Eudragit RS microspheres containing sulphasalazine. Fourier transform-Raman spectroscopy was successfully used as a non-destructive method for qualitative and quantitative microsphere characterisation. The technique provided good agreement with a UVspectrophotometric method in quantifying the amount of drug in microsphere samples. X-ray photoelectron spectroscopy was used to estimate the concentration of sulphasalazine at the microsphere surface for samples produced with or without the use of surfactant. Across a wide range of microsphere drug loadings, the surface drug content remained remarkably constant, but was consistently lower in the samples produced using surfactant. In a parallel programme of work, using gamma scintigraphy, the transit rate of different sizes of radiolabelled materials through the human colon was investigated to determine whether there was an optimal size to maximise colon residence. There was no clear evidence of any difference in the colon residence time of 0.2 mm particles, 5 mm tablets, or 8.4 mm tablets, under normal conditions and during accelerated transit. In healthy subjects, 50% of a dose of 0.2 mm particles resided in the ascending colon for an average of 11 hours. Finally, an in vivo biopharmaceutical evaluation of sulphapyridine-containing Eudragit RS microspheres in the human colon was undertaken. For this study, a neutron activation technique was developed for microsphere radiolabelling. Microspheres could be successfully radiolabelled by incorporation of samarium oxide followed by neutron irradiation. However, it was necessary to minimise the period of irradiation and the amount of incorporated samarium oxide, since high levels of both were found to adversely affect microsphere performance. The in vivo investigation revealed that the colonic bioavailability of sustained-release microencapsulated sulphapyridine was less than 50% of unencapsulated sulphapyridine powder. This shortfall was possibly due to an interaction of the drug with colonic bacteria or in vitro/in vivo differences in microsphere drug release characteristics.